Students’ Mathematical Problem-Solving Ability at Realistic Mathematics Education (RME) - Huda, Muhammad Jamalul; Florentinus, Totok Sumaryanto; Nugroho, Sunyoto Eko (Journal of Primary Education)
This study aims to determine the effectiveness of the Realistic Mathematics Education model on mathematics problem-solving ability of students and analyze the mathematical problem-solving ability of students based on Polya steps. The method used is the sequential explanatory mixed-method design. The sample in this study is the fourth-grade students of Public Elementary School Bintoro 8 and the fourth-grade students of Public Elementary School Bintoro 9. Quantitative data were analyzed using a t-test and N-gain test based on the value of mathematical problem-solving ability. Qualitative data were analyzed through five procedures: data collection, triangulation, reduction, data presentation, and verification. The results showed that the average difference of mathematical problem-solving ability of students experimental class is better than the control class, improvement of mathematics problem-solving ability of students in the experimental class is higher than the control class. In the high category, students can apply the measures to see, plan, d, and check it well. In the medium category students can apply the measures see, plan, do and check, but there is an error in the operation so that the results of any settlement, while in the low category of students has not concluded.